2013
DOI: 10.1080/15459624.2013.818238
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring Study of Dry Cleaning Workers Using Cytogenetic Tests and the Comet Assay

Abstract: Perchloroethylene (PCE) is the main solvent used in the dry cleaning industry worldwide. The aim of the present work was to evaluate the genotoxic potential of occupational exposure to PCE in dry cleaning workers. The study was carried out in 59 volunteers (30 workers, 29 controls). The genotoxic effect was evaluated by analyzing chromosome aberrations (CAs), and micronuclei (MN) and DNA damage (assessed by the comet assay) in peripheral blood lymphocytes. Environmental monitoring of exposure was carried out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…While the genotoxic effects of exposure to PERC have been investigated previously based on chromosomal aberration and micronucleus test, 12 to the best of our knowledge, there is only another human study that used comet assay to evaluate genotoxicity in dry cleaners and found significant early DNA damage in dry cleaners. 8 Despite several animal and in vitro studies on genotoxicity of PERC based on comet assay, there are no conclusive remarks about this issue based on cytogenetic tests. Cederberg, et al , found a weak but significant increase in early DNA damage in rats exposed to PERC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the genotoxic effects of exposure to PERC have been investigated previously based on chromosomal aberration and micronucleus test, 12 to the best of our knowledge, there is only another human study that used comet assay to evaluate genotoxicity in dry cleaners and found significant early DNA damage in dry cleaners. 8 Despite several animal and in vitro studies on genotoxicity of PERC based on comet assay, there are no conclusive remarks about this issue based on cytogenetic tests. Cederberg, et al , found a weak but significant increase in early DNA damage in rats exposed to PERC.…”
Section: Discussionmentioning
confidence: 99%
“…Informed verbal and written consents were obtained from all participants. Sample size calculation was conducted for tail length effect size based on what reported in Everatt study, 8 where the mean of tail length for exposed and non-exposed groups was 10.45 (SD 6.52) and 5.77 (2.31), respectively. The minimum sample size in each group for a power of 80% and a two-sided significance level of 0.05 was 31.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA damage detected by alkaline comet assay was significantly higher in dry-cleaning workers than the controls. Comet assay was found to be a useful method for monitoring populations exposed to the low doses of PCE (22). Toluene is widely used in many industries.…”
Section: Resultsmentioning
confidence: 99%